TRIM Proteins in Therapeutic Membrane Repair of Muscular Dystrophy - Alloush, Jenna (2013)
Muscular dystrophy represents a major unmet medical need as only palliative treatments exist for these debilitating diseases. Since multiple forms of muscular dystrophy arise from compromised sarcolemmal membrane integrity a therapeutic approach that can target this loss of membrane barrier function could be applicable to a number of these distinct genetic diseases. One pathway that presents an excellent opportunity to affect compromised membrane integrity is the process that the cell uses to repair injuries to the plasma membrane. Membrane repair is a conserved pathway where disruptions in the plasma membrane of many different cell types are resealed by trafficking of intracellular vesicles to the injury site where these vesicles can fuse and patch the membrane disruption. Recent discoveries of multiple genes associated with this process in skeletal muscle provide opportunities to target this mechanism to increase membrane repair as a therapy to treat muscular dystrophy. One such gene is a member of the tripartite motif (TRIM) family of proteins, mitsugumin 53 (MG53) or TRIM72, that is an essential component of the membrane repair pathway in striated muscles. Recent results indicate that MG53/TRIM72 protein can be directly applied as a therapeutic agent to increase membrane repair capacity of many cell types and treat some aspects of the pathology in mouse models of muscular dystrophy. There is great potential for the use of recombinant human (rhMG53) in the treatment of muscular dystrophy and other diseases where compromised membrane integrity contributes to the progression of the disease. Other TRIM family proteins may provide additional targets for therapeutic intervention in similar disease states.